2019
DOI: 10.1084/jem.20190945
|View full text |Cite
|
Sign up to set email alerts
|

GM-CSF in inflammation

Abstract: Granulocyte–macrophage colony-stimulating factor (GM-CSF) has many more functions than its original in vitro identification as an inducer of granulocyte and macrophage development from progenitor cells. Key features of GM-CSF biology need to be defined better, such as the responding and producing cell types, its links with other mediators, its prosurvival versus activation/differentiation functions, and when it is relevant in pathology. Significant preclinical data have emerged from GM-CSF deletion/depletion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
189
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(207 citation statements)
references
References 221 publications
4
189
0
1
Order By: Relevance
“…Activin A and other proteins encoded by several GM-CSF-associated gene markers, including MMP12 and CCR2, have been also detected in macrophages from active RA joints [17][18][19]. GM-CSF induces macrophage differentiation and survival from hematopoietic progenitor cells [31,35]. In contrast to M-CSF, GM-CSF is undetectable in the systemic circulation during homeostasis but is produced and active at sites of tissue in ammation, and is a key driver of tissue in ammation and arthritic pain [36,37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activin A and other proteins encoded by several GM-CSF-associated gene markers, including MMP12 and CCR2, have been also detected in macrophages from active RA joints [17][18][19]. GM-CSF induces macrophage differentiation and survival from hematopoietic progenitor cells [31,35]. In contrast to M-CSF, GM-CSF is undetectable in the systemic circulation during homeostasis but is produced and active at sites of tissue in ammation, and is a key driver of tissue in ammation and arthritic pain [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…2A). In fact, the leading edge of the GSEA revealed the genes encoding activin A (INHBA), the metalloproteinase MMP12 and the chemokine CCL17 [31] ( Fig. 2A).…”
Section: Clinical and Demographic Featuresmentioning
confidence: 99%
“…6). One the one hand, GM-CSF can promote myelopoiesis by mobilizing progenitor myeloid cells to sites of SARS-CoV-2 infection, and facilitating their proliferation and differentiation into various innate immune cells, such as monocytes, macrophages and dendritic cells 30 . On the other hand, GM-CSF can also polarize mature myeloid cells into a pro-inflammatory phenotype, and stimulate the production of various proinflammatory cytokines (e.g., TNF, IL-1β and IL-6) and chemokines (e.g., MCP-1) 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found higher levels of circulating GM-CSF-expressing leukocytes in patients with COVID-19 [ 70 ]. Based on the animal studies, clinical trials are underway to study if inhibition of GM-CSF could be beneficial to maintain lung homeostasis, reduce the hyperinflammation, and help in the lung pathogen clearance [ 71 , 72 ]. Contrarily, the benefit of administering the GM-CSF to patients with COVID-19 is also an ongoing debate.…”
Section: White Blood Cells Abnormalities and Covid-19mentioning
confidence: 99%